2016
DOI: 10.1213/ane.0000000000001507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SEER Sonorheometry With Rotational Thromboelastometry and Laboratory Parameters in Cardiac Surgery

Abstract: SEER sonorheometry demonstrates significant correlation with ROTEM for determining Clot Stiffness and assessing Fibrinogen Contribution. SEER sonorheometry results can provide valuable information about the coagulation status in patients undergoing cardiac surgery using CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…We have shown that point-of-care testing using the novel Quantra system provides useful data for guiding transfusion management and have provided reference values corresponding to laboratory triggers for transfusion. In particular, our study suggests that the Quantra demonstrates high negative predictive value for coagulation abnormalities detected by laboratory tests (low platelets, prolonged PT/ aPTT); these results mirror those reported in previous studies [7][8][9] and suggest that the Quantra may be useful for identifying patients where blood component transfusion is not indicated. It also suggests that the Quantra is more useful than thromboelastography and may make the laboratory platelet count redundant for predicting the need for platelet transfusion.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We have shown that point-of-care testing using the novel Quantra system provides useful data for guiding transfusion management and have provided reference values corresponding to laboratory triggers for transfusion. In particular, our study suggests that the Quantra demonstrates high negative predictive value for coagulation abnormalities detected by laboratory tests (low platelets, prolonged PT/ aPTT); these results mirror those reported in previous studies [7][8][9] and suggest that the Quantra may be useful for identifying patients where blood component transfusion is not indicated. It also suggests that the Quantra is more useful than thromboelastography and may make the laboratory platelet count redundant for predicting the need for platelet transfusion.…”
Section: Discussionsupporting
confidence: 89%
“…Viscoelastic testing devices can be used before, during and after bypass to assess the coagulation system, but not all parameters during the three time‐points are equally valid at predicting bleeding and guiding the use of blood products . We only tested blood taken from the arterial cannula, as recommended by Groves et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations